Finding nanotubular halloysite at Lang Dong kaolin deposit, Phu Tho province - Bac, Bui Hoang; Dung, Nguyen Tien (Vietnam Journal of Earth Sciences, 2015)
Halloysite obtained from Lang Dong kaolin deposit, Phu Tho province was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). XRD analysis showed that halloysite (10 Ǻ and 7Ǻ basal spacing) and kaolinite coexist in sample of size fractions <2 mm. SEM and TEM analyses showed that the halloysite has hollow nanotube structures with typical outer diameter of 0.08÷0.30 mm and length of 0.60÷6.00 mm. The mean outer diameter and length are 0.17 and 2.48 mm, respectively. Semi-quantitative analysis using scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM/EDS) showed that the sample consists mainly of Al2O3 and SiO2. Result of formamide (FA) treatment showed that under size fraction <2 mm 50 wt% of the sample was taken by halloysite. The study elucidates the characteristics of mineral components, allowing for more efficient use of this resource.References Berthier, P., 1986: Analyse de I’halloysite. Annales de Chimie et de Physique 32, 332-335. Chipera, S.J., & Bish, D.L., 2002: FULLPAT: a full pattern quantitative analysis program for X-ray powder diffraction using measured and calculated patterns. Journal of Applied Crystallopgraphy 35 (2002) 744-749. Churchman, G.J., 2000: The alteration and formation of soil minerals by weathering. F3-F76 in: Handbook of Soil Science (M.E. Sunner, editor). CRC Press, Boca Ration, Florida. Churchman, G.J., Carr, R.M., 1972: Stability fields of hydration states of a halloysite. American Mineralogist 57, 914-923. Churchman, G.J., Carr, R.M., 1975: The definition and nomenclature of halloysites. Clays and Clay minerals 23, 382-388. Churchman, G.J. and Theng, B.K.G., 1984: Interactions of halloysites with amides: mineralogical factors affect-ing complex formation. Clay Minerals 19, 161-175. Deepak, R., & Agrawal, Y.K., 2012: Multifarious applications of halloysite nanotubes: A review. Reviews on Advanced Materials Science 30, 282-295. Ghanbari, M., Emadzadeh, D., Lau, W.J., Matsuura, T., Ismail, A.F., 2015: Synthesis and characterization of novel thin film nanocomposite reverse osmosis membranes with improved organic fouling properties for water desalination. RSC Advances 5, 21268-21276. Hillier, S., Ryan, P.C., 2002: Identification of halloysite (7Ǻ) by ethylene glycol solvation: the ‘MacEwan effect’. Clay minerals 37, 487-496. Joussein, E., Kruytz, N., Righi, D., Petit, S., Delvaux, B., 2004: Specific retention of radiocesium in volcanic ash soils devoid of micaceous clay minerals. Soil Science Society of America Journal 68, 313-319. Kohymna, N., Fukushima, K. and Fukami, A., 1978: Observation of the hydrated form of tubular halloysite by an electron microscope equipped with an environmental cell. Clays and Clay Minerals 26, 25-40. Mineralogy database: http://webmineral.com/data/Halloysite.shtml#.VmqAFtJ97RZ . Mingliang, D., Baochun, G., Demin, J., 2010: Newly emerging applications of halloysite nanotubes: A review. Polymer International 59, 574-582. Nicolini, K.P., Fukamachi, C.R.B., Wypych, F., and Salvio M.A.S., 2009: Dehydrated halloysite intercalated mechanochemically with urea: Thermal behavior and structural aspects. Journal of Colloid and Interface Science 338, 474-479. Nguyen, T.D., & Nguyen, P., 2006: Geological characteristics and quality of kaolin, feldspar in Thach Khoan area, Thanh Son, Phu Tho. Journal of Mining & Geology Science and Technology 15(7) 65-70 (in Vietnamese). Poppe, L.J., Paskevich, V.F., Hathaway, J.C., and Blackwood, D.S., 2001: A laboratory manual for X-ray powder diffraction. U.S. Geological Survey Open-File Report 01-041, pp. 88. Ravindra, K., Manasi, G., Sheetal, G., Bijoy, K.P., 2012: Halloysite nanotubes and applications: A review. Journal of advanced scientific research 3(2) 25-29. Sunaree, B., Darunee, B., Thongchai, P., Tripob, B., 2011: Characterization ò halloysite from Thung Yai District, Nakhon Si Thammarat Province, in southern Thailand. Songklanakarin Journal of Science and Technology 33(5), 559-607. Wada, S.I., & Mizota, C., 1982: Iron-rich halloysite (10Ǻ) with crumpled lamellar morphology from Hokkaodo, Japan. Clays and Clay minerals 30, 315-317. Yariv, S. and Shoval, S., 1976: Interaction between alkali-halides and halloysite: I.R. study of the interaction between alkali-halides and hydrated halloysite. Clays and Clay Minerals 24, 253-561.